The legal expertise procedure of legal acts in Ukraine - Філик, Наталія Володимирівна; Рибікова, Ганна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article is about a new approach to defining the stages of the procedure of the legal expertise of legal acts in Ukraine with the allocation of tasks, participants, content of each stage and characterization of a conclusion of legal expertise of legal acts. The procedure of conducting of the legal expertise of legal acts is the regulated by the law activities of authorized bodies and their officials on the organization and implementation of analysis, verification and evaluation of the object of expertise for compliance with the legal criterion of quality with the compilation and submission of a conclusion of the expertise to the customer. The stages of legal expertise of legal acts include: registration of relations between the customer and the organizer of legal expertise of legal acts; preparation of legal expertise of legal acts; conducting of legal expertise of legal acts; receiving and realization of results of expertise by the customer. This approach allows to cover the whole complex of relations, starting from the initiative of the customer and ending with the implementation of the conclusion of the expertise. There are sub-stages of the stage of legal expertise of legal acts: conceptual assessment, systemic and legal assessment, comparative legal assessment, technical and legal assessment, drawing up the conclusion of the expertise. To the list of these sub states we consider it necessary to add to the subject of verification of the object of expertise using the hermeneutic method to comply with the "will of the legislator. "The concept of "conclusion of legal expertise of legal acts" can be defined as the result of conducting legal expertise of legal acts on the basis of a definite methodology, which contains clear answers to the questions of conformity of the object of expertise with the necessary legal criteria of quality and proposals for elimination of identified deficiencies.